2015
DOI: 10.3906/biy-1507-55
|View full text |Cite
|
Sign up to set email alerts
|

DNA protective and antioxidative effects of melatonin in streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus is a chronic disease characterized by elevated blood sugar levels. In diabetic patients, oxidative stress induced by the presence of excessive free radicals is closely associated with chronic inflammation, leading to potential tissue damage. Melatonin (MEL) is a compound synthesized by the pineal gland and a scavenger of free radicals. The aim of this study was to research the effects of MEL on oxidative stress and its DNA protective effects in streptozotocin-induced diabetic rats. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…The current study's findings demonstrated that STZ injection caused the blood glucose level in the diabetic group to significantly increase as contrasted with control group, while glycated haemoglobin levels substantially decreased. These findings concur with those of Sekkin et al (15) 's research who reported a single STZ injection results in the onset of diabetes mellitus., which is identified by raised blood sugar, glycated haemoglobin, and drop serum insulin levels. This happened because STZ generated an inflammatory response that resulted in macrophage and later lymphocyte infiltration, damaged the islets cells, destroyed the cells within twenty-four hours, and triggered an immune response.…”
Section: Discussionsupporting
confidence: 93%
“…The current study's findings demonstrated that STZ injection caused the blood glucose level in the diabetic group to significantly increase as contrasted with control group, while glycated haemoglobin levels substantially decreased. These findings concur with those of Sekkin et al (15) 's research who reported a single STZ injection results in the onset of diabetes mellitus., which is identified by raised blood sugar, glycated haemoglobin, and drop serum insulin levels. This happened because STZ generated an inflammatory response that resulted in macrophage and later lymphocyte infiltration, damaged the islets cells, destroyed the cells within twenty-four hours, and triggered an immune response.…”
Section: Discussionsupporting
confidence: 93%
“…The over generation of ROS, LPO, and diminished tissue concentrations of SOD, CAT, and GSH were reported in both clinical and experimental models of diabetes ( 23 ). Similar findings were reported in different tissues, such as diabetic rat’s liver, kidney, and pancreas ( 24 ), heart ( 25 ), as well as blood ( 26 ).…”
Section: Discussionsupporting
confidence: 85%
“…It is a direct scavenger of free radicals as well as a co-substrate for peroxide detoxification by GPX. Increased GSH level might have been sustained to counteract fast-generating oxygen radicals and concomitantly protect tissue cells from ROS and peroxides ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that induction of diabetes decreased the plasma GSH concentration in the rats and administration of melatonin increased the GSH levels significantly near to healthy control rats. Sekkin et al demonstrated that induction of diabetes caused depletion in GSH in the pancreas tissue and treatment with melatonin for 6 weeks elevated the GSH levels significantly [34]. Klepac et al also, reported that melatonin (20 mg/kg, ip) increased the plasma GSH concentration in diabetic rats by 9% after a single injection [7].…”
Section: Discussionmentioning
confidence: 97%